Under fungal attack on a metalliferous soil: ROS or not ROS? Insights from Silene paradoxa L. growing under copper stress. (March 2016) - Taiti, Cosimo; Giorni, Elisabetta; Colzi, Ilaria; Pignattelli, Sara; Bazihizina, Nadia; Buccianti, Antonella; Luti, Simone; Pazzagli, Luigia; Mancuso, Stefano; Gonnelli, Cristina
Abstract: We investigated how the adaptation to metalliferous environments can influence the plant response to biotic stress. In a metallicolous and a non-metallicolous population of Silene paradoxa the induction of oxidative stress and the production of callose and volatiles were evaluated in the presence of copper and of the PAMP fungal protein cerato-platanin, separately and in combination. Our results showed incompatibility between the ordinary ROS-mediated response to fungal attack and the acquired mechanisms of preventing oxidative stress in the tolerant population. A similar situation was also demonstrated by the sensitive population growing in the presence of copper but, in this case, with a lack of certain responses, such as callose production. In addition, in terms of the joint behaviour of emitted volatiles, multivariate statistics showed that not only did the populations respond differently to the presence of copper or biotic stress, but also that the biotic and abiotic stresses interacted in different ways in the two populations. Our results demonstrated that the same incompatibility of hyperaccumulators in ROS-mediated biotic stress signals also seemed to be exhibited by the excluder metallophyte, but without the advantage of being able to rely on the elemental defence for plant protection from natural enemies. Highlights: Silene paradoxa plants from metalliferous and nonmetalliferous soil were studied. Plants were exposed to Cerato-platanin in presence/absence of Cu in culture media. ROS response was fully present in nonmetallicolous plants only in the absence of Cu. Similar ROS response in metallicolous plants with or without Cu. Abstract : The adaptation to high concentrations of copper was found to interfere with the ordinary ROS-mediated response to fungal attack in an excluder metallophyte.